1963
DOI: 10.1002/j.1537-2197.1963.tb10645.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Cytohistological Studies on Inhibition and Promotion of Stem Growth in Chrysanthemum Morifolium

Abstract: Sachs, R. M. (U. California, Davis), and A. M. Kopranek. Comparative cytohistological studies on inhibition and promotion of stem growth in Chrysanthemum morifolium. Amer. Jour. Bot. 50(8): 772‐779. Illus. 1963.—The present study with Amo, CCC, and Phosfon,3 3 substances which inhibit stem elongation, shows that all inhibit subapical cell expansion and division in Chrysanthemum morifolium var. ‘Indianapolis Yellow.‘ Furthermore, GA,3 in preventing the inhibition of stem elongation, maintains subapical activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

1964
1964
2014
2014

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Others (4,9,14,20,21), however, have found many instances in which there was little or no mutual antagonism between the retardants and gibberellins or auxins. They have felt that the inhibitory effects should not be restricted to the hormonal level.…”
mentioning
confidence: 99%
“…Others (4,9,14,20,21), however, have found many instances in which there was little or no mutual antagonism between the retardants and gibberellins or auxins. They have felt that the inhibitory effects should not be restricted to the hormonal level.…”
mentioning
confidence: 99%
“…These values are 10-12 hr longer than those which we obtained from normal or GA-treated dwarf watermelon seedlings. In the rosette plant Samolus parviflorus, Sachs et al (1959) reported a cell generation time of 24 hr in subapical meristem cells partially synchronized by GA treatment. Cell cycle times obtained from root meristems of several species at temperatures between 20-30 C (Burholt and Van't Hof, 1971;Evans and Savage, 1959;Van't Hof and Sparrow, 1963;Wimber, 1966) are generally shorter than the above values for shoot meristems.…”
Section: Materials and Methods-plant Materials Andmentioning
confidence: 99%
“…Studies employing GA-responsive genetic dwarfs (Basford, l 1961;Greulach and Haesloop, 1958;Loy and Liu, 1974;Okuda, 1964), rosette plants (Bernier, Bronchart, and Jacqmard, 1964;Sachs, Bretz, and Lang, 1959), and plants treated with growth retardants (Sachs and Kofranek, 1963;Sachs et al, 1960) have provided convincing evidence that stimulation of cell division in the subapical meristematic zone is a common feature of gibberellinmediated increases in stem elongation. Burholt and Van't Hof (1971) emphasize the need to examine several parameters, such as mitotic index, duration of the cell cycle and the number of proliferating cells to provide an accurate assessment of cell kinetics in meristematic tissues.…”
mentioning
confidence: 99%
“…Such gains may be explained by the direct role of growth retardants used in retarding stem elongation by reducing cell division and extension in the subapical meristematic zone of the stem (Sacks and Kofranek, 1963) or by inhibition of cytokinin and gibberellin biosynthesis (Million et al, 1999). Similar observations were also postulated by Wei and Han (1997), Yewale et al (1997) and Yoo et al (1999) on chrysanthemums.…”
Section: Photo 1 Effect Of Pp-333 At 100 Ppm (Left) Compared To Contmentioning
confidence: 99%
“…Among of these plants may be chrysanthemums which usually need staking to stay upright. In this respect, Sacks and Kofranek (1963) have shown that Amo-1618, CCC and phosphon-D, all inhibite subapical cell expansion and division in Chrysanthemum morifolium. Qrunfieh and Al-Wir (1987) elicited that PP-333 at 1000, 2000 and 4000 ppm as soil drench significantly reduced shoot length in five chrysanthemum cvs., namely: Tom Pearce, PR.…”
Section: Introductionmentioning
confidence: 97%